Analisis Efektivitas Kepemimpinan terhadap Kinerja Pegawai di Masa Pandemi Covid-19 (Studi pada Dinas Perindustrian dan Perdagangan Kota Magelang) - Krisma Adistia; Dian Marlina Verawati (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This review intends to test and investigate the viability of initiative on worker execution in the new typical time at the Department of Industry and Trade of Magelang City. Information was gathered by dispersing polls to 79 representatives of the Department of Industry and Trade of Magelang City. The scientific technique in this review utilizes the SPSS type 21 application drive with basic straight relapse testing and t test. The aftereffects of this review clarify that the administration viability variable has an impact of 19.3% on the worker execution variable. In view of the aftereffects of the t-test, it clarifies that administration adequacy essentially influences worker execution where the t-count esteem is 4.295 which is more prominent than the t-table worth of 1.668, though the importance esteem is 0.000 so the worth is more modest than 0.05.